Database for provenance determination of Roman-time stone products from Ig area - Brajkovič, Rok; Žvab Rožič, Petra; Gale, Luka (Geologija, 2025)
The stone products from the Roman-time found in the Ig area were mainly made from micritic and peloidal limestone. The provenance of these products has been only roughly defined so far, mainly due to the lack of detailed microfacies descriptions, study of microfossils and missing geochemical analyses from the previously identified or proposed areas of Roman quarries. This database fills this gap and provides a detailed insight into the lithological and geochemical composition of the limestone found in Podutik, Staje, Ig, Podpeč, Jezero near Podpeč, on the hill of St. Ana and at Ledenica near Planinca. The sedimentological logs represent parts of the Lower Jurassic Podbukovje Formation, specifically the members E1 – laminated micritic and oolitic limestone, E2 – fossiliferous limestone, E3 – crinoid limestone belonging to the Podbukovje Formation, and E4 – oolitic limestone and dolomite belonging to the Laze Formation. For purposes of comparison, accessible stone products from the Ig area were studied using the same methods. The applied methodology includes geological mapping, detailed sedimentological description of sediment sequences and macroscopic examination of samples, optical microscopy for the analysis of lithofacies, microfacies and benthic foraminifera, cathodoluminescence analysis, analysis of strontium isotope ratio values, stable carbon and oxygen isotope ratio values, determination of mineral composition and content of major, minor and trace elements.